Sistem Edukasi Pengenalan Rumus Matematika Menggunakan Aughmented Reality Berbasis Android - Yulia; Pratiwi, Andriani; Arnomo, Sasa Ani (Jurnal Sistim Informasi dan Teknologi, 2022)
The introduction of spatial media, especially in mathematics, is still often applied to learning module media such as books or whiteboard media as happened. In this case it is less effective because students are less able to absorb what is conveyed by the teacher because the media is still in the form of 2D images. This study aims to build learning augmented reality with markerless method based on android. With the application of augmented reality objects in the recognition of spatial shapes can be used as 3D images. The spatial applications that will be made are cubes, blocks, triangular prisms, triangular pyramids, rectangular pyramids, cones, spheres and regular hexagon prisms. The final result obtained is an educational application for the introduction of mathematical formulas, especially in building spaces using Android-based augmented reality, and in the form of a marker book. It is possible that this technology can be used as a tool for more innovative methods of introducing mathematical geometric formulas. By shining on the rear camera on the marker book, users can immediately see in 3D on the smartphone screen the shape of the shapes and formulas that exist in real time. This will be an interesting lesson, especially for fifth graders at SDIT At Taubah Batam.